The Importance of Business Communication in Maintaining Consumer Trust in the Era of Disruption - M. Fahri Ramadhan; Saprida Saprida; Fadilla Fadilla; Havis Aravik; Ahmad Tohir (Penerbit dan Percetakan CV.Picmotiv, 2026)
The era of disruption, marked by advances in digital technology, has changed the way businesses interact with their consumers. To maintain consumer trust, businesses must implement effective business communication. The purpose of this study is to examine the importance of business communication in maintaining consumer trust in the era of disruption. The method used is a qualitative descriptive approach to conduct literature research. This was done by reviewing various relevant journals and scientific sources. The results show that transparent, responsive, and consistent business communication can increase consumer trust and loyalty. Digital media is also an important strategy for building closer relationships with customers. Therefore, to maintain their competitiveness and maintain customer trust, companies must create communication strategies that are responsive to technological advances.